A novel aminothiazole-based cyclotriphosphazene derivate towards epoxy resins for high flame retardancy and smoke suppression. (August 2021) - Ning, Kai; Zhou, Lin-Lin; Zhao, Bin
Highlights: A novel aminothiazole-based cyclotriphosphazene derivate (HTACP) is successfully synthesized. HTACP shows high efficiency for simultaneously enhancing flame retardancy and smoke suppression for epoxy resin. HTACP presents a special bi-phase flame retardant mechanism. Abstract: There is a need to develop halogen-free flame retardants for epoxy resin (EP) to reduce the fire risks. Cyclotriphosphazene-based derivatives have been proved to be effective phosphorous-containing flame retardants. This article demonstrates the preparation and application of a novel aminothiazole-based cyclotriphosphazene derivate (hexathiazoleaminocyclotriphosphazene, HTACP) for EP. After characterizing by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance, and high-resolution mass spectroscopy, HTACP is utilized as a reactive flame retardant for EP. HTACP effectively inhibits the decomposition of EP and improves the char yield during heating according to the thermogravimetric analysis (TGA) results. HTACP also changes the dynamic thermomechanical behaviors of EP according to dynamic mechanical analysis (DMA). With the incorporation of 5 wt% HTACP, EP passes UL-94 V-0 rating during the vertical flame testing and obtains an increased limiting oxygen index of 28.5% with only 0.73% phosphorous content. The cone calorimeter testing results show that HTACP endows EP with beyond 50% reduction of peak heat release rate and total smoke production. The results of smoke density chamber tests also prove the excellent smoke-suppression effects for EP. Furthermore, scanning electron micrograph, X-ray photoelectron spectroscopy, TG-FTIR, and pyrolysis gas chromatography/mass spectrometry are used to analyze the chars and pyrolysis behaviors of EP/ HTACP. The phosphazene structure in HTACP molecule is left in the condensed phase, which promotes forming protective chars, while the multiple nitrogen- and sulfur-containing volatiles derives from aminothiazole groups act dilution effects in the flame zone. This novel aminothiazole-based cyclotriphosphazene shows a high efficiency for reducing fire hazards of EP through a bi-phase mechanism.